BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Advances in Plant Disease Management. Editors: Udit Narain, Kumud Kumar and Mukesh Srivastava. Advance Publishing Concept, New Delhi, 2000, 365 pp, Price Rs.550.